Apakah Desain Produk, Brand Image Dan Kemudahan Transaksi Mempengaruhi Keputusan Pembelian Sepeda Motor Honda Vario - Sukma Bayu; Rayhan Gunaningrat (STIKes Ibnu Sina Ajibarang, 2024)
Motorcycle sales in Indonesia increased by 1.24% in October 2023, reaching 516,293 units, despite experiencing an annual decline of 3.96%. Cumulative figures for January-October show a growth of 26.22%, reaching 5,237,976 units. The research focuses on the Honda Vario motorcycle, aiming to understand the influence of design, brand image, and transaction convenience on purchase decisions. A quantitative research method was employed through surveys and questionnaires involving 93 consumers. Regression analysis indicates a positive relationship between product design, brand image, transaction convenience, and purchase decisions. The results highlight the importance of these factors in influencing consumer preferences for motorcycles, providing insights into market dynamics, and showcasing Honda's success in maintaining its dominance.